How to make collaboration work : powerful ways to build consensus, solve problems, and make decisions - Straus, David (Berrett-Koehler, 2002)
Every day, we must work with others to solve problems and make decisions. Yet these efforts at collaboration often leave us frustrated. This work reveals why collaborative problem-solving seems so hard, and describes five time-tested principles for making collaborative efforts more joyful.